1997
DOI: 10.1023/a:1024868632543
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study evaluated the potential relationship between posttraumatic stress disorder (PTSD) and sexual problems. The Golombok Rust Inventory of Sexual Satisfaction was mailed to combat veterans currently in treatment at an outpatient PTSD clinic. Completed questionnaires were received from 90 patients. Results indicated that over 80% of subjects were experiencing clinically relevant sexual difficulties. Impotence and premature ejaculation were the most frequently reported problems that have corresponding psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…PTSD is associated with poor sexual functioning in multiple domains: desire, arousal, orgasm, activity and satisfaction. These findings confirm those of Kaplan [1, 2], Letourneau et al [3], Litz et al [22]and Solursh and Solursh [23]. One possible explanation for these findings is that PTSD serves as a moderating variable between an initial trauma and sexual problems.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…PTSD is associated with poor sexual functioning in multiple domains: desire, arousal, orgasm, activity and satisfaction. These findings confirm those of Kaplan [1, 2], Letourneau et al [3], Litz et al [22]and Solursh and Solursh [23]. One possible explanation for these findings is that PTSD serves as a moderating variable between an initial trauma and sexual problems.…”
Section: Discussionsupporting
confidence: 90%
“…Kaplan [1, 2]has shown that sexual problems are prevalent among PTSD patients. Letourneau et al [3]reported that over 80% of PTSD patients studied were experiencing clinically relevant sexual difficulties. Impotence and premature ejaculation were the most frequently reported problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that sexual problems are highly prevalent in psychiatric outpatients, including PTSD patients [1, 2, 3, 4, 5]. Letourneau et al [3] reported that over 80% of PTSD patients studied were experiencing clinically relevant sexual difficulties while erectile dysfunction and premature ejaculation were the most frequently reported problems. It was suggested that PTSD might be a significant risk factor for sexual problems [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that sexual behavior problems may apply only to a subset of individuals with a specific traumatic exposure: victims of sexual abuse. However, previous studies have reported high rates (over 80%) of clinically significant sexual problems in male combat veterans with PTSD (Letourneau, Schewe, & Frueh, 1997), as well as a significant association between PTSD and sexual problems in female crime victims (Letourneau, Resnick, Kilpatrick, Saunders, & Best, 1996). Further work to field test and calibrate these items will determine whether they do fall within these clusters, whether they are appropriate for inclusion in a CAT, and whether a CAT can accurately assess and monitor PTSD symptoms using a smaller number of items than paper-and-pencil tests.…”
Section: Discussionmentioning
confidence: 90%